Agency in entrepreneurship: preparing entrepreneurship theory for another view of context - Melin, Erik; Gaddefors, Johan (2023)
PurposeThe purpose of this article is to explore how agency is distributed between human actors and nonhuman elements in entrepreneurship.Design/methodology/approachIt is based on an inductive longitudinal case study of a garden in a rural community in northern Sweden. The methodology includes an ethnography of the garden, spanning the course of 16 years, and a careful investigation of the entrepreneurial processes contained within it.FindingsThis article identifies and describes different practices to explain how agency is distributed between human actors and nonhuman elements in the garden's context. Three different practices were identified and discussed, namely “calling”, “resisting”, and “provoking”.Originality/valueAgency/structure constitutes a longstanding conundrum in entrepreneurship and context. This study contributes to the on-going debate on context in entrepreneurship, and introduces a posthumanist perspective—particularly that of distributed agency—to theorising in entrepreneurship. Rather than focussing on a human (hero)-driven change process, induced through the exploitation of material objects, this novel perspective views entrepreneurship as both a human and a nonhuman venture, occurring through interactions located in particular places and times. Coming from the agency/structure dichotomy, this article reaches out for elements traditionally established on the structure side, distributing them to the agency side of the dichotomy. As such, it contributes to an understanding of the agency of nonhuman elements, and how they direct entrepreneurship in context. This theoretical development prepares entrepreneurship theories to be better able to engage with nonhuman elements and provides example solutions for the ongoing climate crisis.